Predação de ovos de Tuta absoluta (Lep.: Gelechiidae) no desenvolvimento e sobrevivência de Campyloneuropsis infumatus e Engytatus varians (Hem.:Miridae) - Soares, Marianne Araújo (2015)
Predatory bugs from Family Miridae have received currently great attention as potential candidates for biological control agents. Some species are being commercialized and used to control Tuta absoluta (Lep:. Gelechiidae), and other pests in tomato crops in Europe. However, little is known about the vast majority of species from this family, such biological and behavioral aspects and their role as potential control agent. The objective of this study was to determine the life time predation of Campyloneuropsis infumatus and Engytatus varians (Hem.: Miridae) on eggs of Tuta absoluta (Lep.: Gelechiidae). Fifty newly emerged nymphs of E. varians and C. infumatus were individualized in Petri dishes (5 cm diameter) contained a tomato leaflet and different densities of T. absoluta eggs and kept at 24 ± 1 °C, 70 ± 10% RH and 12h photophase. The parameters evaluated were developmental time and survival by instar and nymphal, egg predation, weight, size and sex ratio of newly emerged adults. Predation of eggs of T. absoluta was increasing during the development of each instar, and increased as they approached the adult stage. The duration time of the 5th instar was longer followed by the 1st, 2nd, 3rd and 4th nymph instars. The nymphal developmental time of C. infumatus and E. varians was not different significantly. The nymphal survival of the two predator species was more than 90% having T. absoluta eggs as food. The adults of C. infumatus had lower weight and size compared to those of the species E. varians. The sex ratio of C. infumatus was biased for females than males. The eggs of T. absoluta were accepted by the two predator species and provided complete nymphal developmental time and high survival, indicating to be adequate and good nutritional food source to the immature stages of C. infumatus and E. varians.